Effects of alternative feeding strategies for feedlot cattle on meat quality - Phelps Ronningen, Kelsey (Kansas State University, 2017)
American beef producers use a multitude of production regimens, with new products constantly becoming available to producers that could ultimately produce beef that fits niche markets. Additionally, U.S. producers employ the use of two exogenous growth promotants (ExGP), anabolic implants and β-adrenergic agonists, to maximize production efficiency. This body of work examined effects of different production strategies on beef quality. In the first study, steers were fed a conventional diet or a diet containing two supplements of the Programmed Nutrition Beef Program (PN) and each diet was fed with or without ExGP. There were no adverse effects on color, but use of ExGP negatively impacted tenderness of steaks. However, the inclusion of the PN supplements decreased purge loss of loins during aging and decreased cook loss of beef steaks. The decrease in purge and cook loss may be intriguing for retailer who purchase-in and cook products as they could specify a demand for beef from animals in this program to potentially save on product losses. Researchers have examined strategies to increase omega-3 fatty acids within beef, as omega-3 fatty acids are health beneficial. The second study examined impacts of feeding increasing levels of a docosahexaenoic acid (DHA)-rich microalgae to heifers on fatty acid profiles, color stability, and palatability of the LM and color and . Feeding increasing levels of microalgae meal quadratically increased total omega-3 PUFA, with increases in DHA content up to 850% and eicosapentaenoic acid (EPA) up to 340% at the greatest feeding level. Although feeding microalgae changed fatty acid profiles to be more health beneficial, color and flavor were adversely affected. At the end of display, steaks from heifers fed the greatest amount of microalgae had reduced a* (redness) values and increases in surface metmyoglobin (discoloration) formation. Panelists detected more off-flavors as the level of microalgae meal increased in the diet. Poor color stability and increases in off-flavors were due to increased oxidation products in these steaks, but problems could be mitigated by inclusion of antioxidants in the diet. The third study presented examined effects of feeding antioxidants to steers fed microalgae meal on color and palatability of Longissimus lumborum steaks. Steers were fed vitamin E at a level over their nutritional need and a selenium-yeast product in addition to feeding microalgae. Again, feeding microalgae without antioxidants in the diet negatively impacted color during display, but feeding antioxidants significantly improved the color stability. There were no off-flavor differences between steaks from steers fed the diet containing only microalgae and diet containing microalgae with antioxidants. Increasing the antioxidant content of the finishing diet when microalgae was fed is feasible way to increase the color stability of steaks and decrease off-flavors of Longissimus lumborum steaks.
Keywords: Color stability; Longissimus lumborum; Microalgae; PalatabilityBeef